Discrimination of marine polychaete species of different harvest times using FTIR metabolomics - Wijaya, I Dewa Made Rizky; Idris, Izwandy; Wan Ismail, Wan Iryani; Asari, Asnuzilawati (Malaysian Institute of Chemistry, 2024)
Marine polychaetes have gained prominence in the study of their potential bioactivities and structurally intriguing compounds. However, studies on the chemical profile of polychaete species are still lacking. This study aimed to conduct the chemical profile of marine polychaete species subjected to different harvest times using Fourier transform infrared (FTIR) metabolomics and proton nuclear magnetic resonance (1H NMR) analysis. In this study, two marine polychaetes, namely Diopatra claparedii and Marphysa moribidii, were collected and analyzed. Multivariate data analysis of the FTIR data via orthogonal partial least squares discriminant analysis (OPLS-DA) revealed four distinct clusters of the polychaetes were formed based on their different harvest times. Furthermore, organic acids, fatty acids, and aromatic compounds were found to be important in discriminating the polychaete species based on 1H NMR characteristic signals. FTIR metabolomics results suggest that the first and second quarters of the year are the best harvesting times due to their chemical profile consistency. FTIR metabolomics is a useful preliminary analytical tool to discriminate polychaete samples from different harvest times and predict new batches of samples. These results provide basic information on the metabolite variations in polychaetes from different species and harvest times, which might be useful for future applications (e.g., drug discovery and climate change study). © 2024 Malaysian Institute of Chemistry. All rights reserved.